Trust as a mediator between customer experience and repurchase intention: Evidence from TikTok Shop Users - Ariandi, Muhamad Amir; Rinaldi, Muhammad (Priviet Social Sciences Journal, 2025)
This study investigated the influence of customer experience on repurchase intention among TikTok Shop users, with trust acting as a mediating factor. Employing a quantitative approach and an explanatory research design, the study surveyed 100 respondents who had made at least two purchases on the TikTok Shop within the preceding six months. Data were gathered through an online questionnaire using a 5 point Likert scale and analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS software. The findings indicate that customer experience exerts a positive and significant effect on trust but does not have a direct impact on repurchase intention. Conversely, trust has a positive and significant effect on repurchase intention, and fully mediates the connection between customer experience and repurchase intention, underscoring the essential role of trust in building customer loyalty on social commerce platforms.